PENGARUH PEMBERIAN KOMPOS SAMPAH ORGANIK TERHADAP PERTUMBUHAN DAN HASIL BERBAGAI VARIETAS KEDELAI (Glycine max (L.) Merill) - Erma Cahyani; AF Aziez AF Aziez; Haryuni Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
Soybean is the main food for the State of Indonesia which is widely used as raw material for tempeh, soy, milk, etc., therefore the Government effort to improve the productivity of soybeans, many ways to increase yield, one of them using a variety of qualified and certified, besides using composting organic waste with sewage or garbage memanfaafan residing within us to be processed into compost, serves as the decomposition of trace substances in the soil so the soil is fertile and cultivated will be crumbly. Compost provides nutrients to plants. With the correct dosage in the administration aimed to efisiens compost and energy costs up to obtain maximum results peningakatan. Research conducted in the village of Dukuh Damu , District Lebaksiu, Tegal regency, Central Java Province. When the study was conducted from July 2009 until September 2009. Experiments using Randomized Complete Block Design (Block design) with split plot method. Factor I as the Main Plot was variety, consists of 3 levels, namely Vanietas Willis (VI), Varieties Lokon (V2), Varieties Grobogan (V3) as a Sub-Plot of Factor II is a dose of compost organic waste, consisted of 4 levels, namely Dose 0 tonnes / ha (DO), Dose 2 tons / ha (AT), dose 5 tons / ha (D2), dose 8 tons / ha (D3). Research results indicate the use of soybean varieties and by providing Grobogan waste compost dose of 8 tons / ha gave the maximum results, but results are not much different with the use of waste compost dose of 5 tons / ha, viewed in Analysis Farming using organic waste compost dose of 5 tons / Ha more profitable